Real Time Optical Vascular Imaging: A Potential Technique for the Diagnosis of Mucosal Disease Including Early Oral Cancer. Issue 1 (February 2016) - Bastos, Pedro; Cook, Richard
Early detection of oropharyngeal carcinoma is imperative in order to minimise morbidity and increase survival rate, but most of these patients present to the specialist with already advanced stages of malignancy, when the prognosis is relatively poor. General dental practitioners and dental care professionals have a unique opportunity during routine examination to detect any suspicious lesions. However, we continue to rely mostly on conventional examination, which is known to have limitations. There are diagnostic adjuncts available to help detect oral squamous cell carcinoma (OSCC) and oral potentially malignant disorders (OPMD), such as vital staining, brush cytology and macroscopic light-based detection techniques, discussed elsewhere in this issue. However a recent meta-analysis demonstrated that these techniques are not reliable enough as standalone diagnostics and that conventional biopsy remains the diagnostic gold standard. This article shows a new imaging technique which has the potential to detect early signs of oral cancer. This technique is based on the use of green light which allows the observation of oral microvasculature. General dental practitioners and dental care practitioners have a privileged opportunity during routine examination to detect any suspicious lesions in the head and neck region and refer when necessary to specialist care. However, they rely mostly on conventional examination, which is known to be insufficient for the detection of early signs of malignancy. There are diagnostic adjuncts available to help detect oral cancer and oral premalignant disorders, such as vital staining, brush cytology and macroscopic light-based detection techniques, but a recent meta-analysis has concluded that alone, these are not reliable enough to make a full tissue diagnosis. In the main, their value is more as a guide to indicate need for and to locate sites for conventional biopsy, which remains the diagnostic gold standard. However, biopsy also has inherent limitations such as sample handling and site errors and is associated with patient morbidity at every sampling event. The authors have developed and tested a new real-time optical vascular imaging technique (RTOVI) to observe the gingival microvasculature as a direct reporter of local tissue function and behaviour. In addition to direct imaging, the reliability of a potential image analysis method, developed for microvascular images, was assessed. The images were assessed for number of capillaries, capillary area (CA), total capillary area (TCA) and aspect ratio (AR). The mean number of capillaries found in our study (45.06 per mm 2 ) which was higher than figures identified in previous 'same-location' oral mucosal studies (15.42 per mm 2 ). This may reflect the wide variation between individuals and potentially improved resolution and contrast optics between studies. This small study suggests that mean values in CA, TCA and AR may be reliable parameters for thresholding normal values, for comparison between individuals and for the assessment of the microvasculature over time. This assessment of normal is essential to pave the way for further studies involving inflammatory and mitotic lesions.